Molecular cloning, expression, and purification of the tick salivary serpin IRS-7 - Pylypchuk, Solomia (Jihočeská univerzita, 2022)
The aim of this thesis was to produce a recombinant IRS-7 using an Escherichia coli expression system along with SUMO fusion protein, purify it, and test this protein for activity in coagulation and protease inhibitor assays to be able to draw early conclusions about its functions in tick-host interactions.
Molecular cloning, expression, and purification of the tick salivary serpin IRS-7
Keywords: IRS-7; serpin; coagulation; IRS-7; serpin; coagulation